Digital Game-Based Learning in Enhancing English Vocabulary: A Systematic Literature Review - Prastiwi, Fitri Dwi; Lestari, Tria Dewi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
This study explores key factors influencing the effectiveness of Digital Game-Based Learning (DGBL) in enhancing English vocabulary acquisition among EFL learners. Using a Systematic Literature Review (SLR) under the PRISMA framework, a total of 206 articles were found, but only 18 were eligible for peer review. We chose a range of years published between 2016 and 2025 to ensure the inclusion of the latest research findings and methodologies that reflect current trends and technological advances in the field. Results show that DGBL significantly boosts vocabulary learning by increasing motivation, engagement, and retention. Technological aspects like interactivity, accessibility, adaptive features, and pedagogical elements such as self-regulated learning and emotional engagement are critical. Cognitive Load Theory helps explain the role of game complexity and scaffolding. DGBL faces challenges like digital literacy gaps and infrastructure issues despite its benefits. The study offers practical insights for educators and recommends further research on AI-driven games and long-term motivation in EFL settings.